First record of Odontanthias unimaculatus (Tanaka 1917) (Perciformes: Serranidae) from Indonesia - TEGUH PERISTIWADY (Biodiversitas Journal of Biological Diversity, 2011)
Peristiwady T (2011) First record of Odontanthias unimaculatus (Tanaka 1917) (Perciformes: Serranidae) from Indonesia. Biodiversitas 12: 136-140. Seven specimens of O. unimaculatus were collected from Bitung, North Sulawesi between 7 January and 18 August 2009. They were caught from depths of about 100 m in association with other deep water fishes as Epinephelus, Pristipomoides and Etelis. O. unimaculatus was most similar to O. grahami, in sharing the following characters: dorsal fin soft rays 14, anal fin soft rays 7, scales on lateral line 36-37 and gill rakers on upper limb 13-14. If caudal fin shape and coloration were ignored, O. unimaculatus would seem most closely related to O. tapui and O. chrysostictus. Their body proportions were nearly the same. However the laterspecies had longer body width, third dorsal and second anal spine but had shorter longest dorsal ray length, longest anal rays, caudal-fin length and caudal concavity. Other little different characters of O. unimaculatus with other seven species were the proportion of upper jaws length and proportion of body depth. Initially this species was described as new species from Tanabe, Wakayama Prefecture, Japan. Other specimens were reported from Suruga Bay, Japan, Keelung and Kaohsiun, Taiwan and Lubang Island, Philippines and now recorded also in Bitung, North Sulawesi, Indonesia.